Arteriolosclerosis CSVD: a common cause of dementia and stroke and its association with cognitive function and total MRI burden - Hua, Min; Ma, Ai-Jin; Liu, Zhi-Qing; Ji, Li-Li; Zhang, Jin; Xu, Yuan-Feng; Chen, Wen-Ya; Mao, Lun-Lin (Frontiers in Aging Neuroscience, 2023)
Objective Arteriolosclerosis cerebral small vessel disease (CSVD) is a common type of CSVD. this study is to explore the factors associated with cognitive function and total MRI burden related to the disease.The demographic characteristics, clinical manifestations, cognitive function score, Barthel Index (BI), blood test index, and follow-up results of arteriolosclerosis CSVD patients treated for the first time in our hospital from January 2014 to August 2022 were collected. White matter hyperintensity (WMH) Fazekas score, total MRI burden, and cerebral atrophy grade were evaluated according to brain MRI findings.Factors associated with CSVD cognitive function were analyzed by binary logistic regression. The correlative factors related to the total MRI burden of CSVD were analyzed by ordered multiple logistic regression.Results A total of 146 patients were included in this study, of which 132 cases (90.4%) had hypertension.There were 108 patients (74.0%) with cognitive dysfunction, 97 patients (66.4%) with balance and gait disorders, and 83 patients (56.8%) with moderate to severe dependence in daily life (BI≤60 points). Out of 146 patients, 79 (54.1%) completed clinical and imaging follow-ups for a median of three years. The number of patients with cognitive impairment and BI≤60 points after follow-up significantly increased compared to the first admission (P < 0.001). There were also significant differences in total MRI burden (P = 0.001), WMH Fazekas score, and cerebral atrophy grade (P < 0.001). Mean age (P = 0.012), median deep WMH Fazekas score (P = 0.028), and median deep (P < 0.001) and superficial (P =0.002) 2 cerebral atrophy grade of patients with cognitive impairment at first admission were all higher than those with non-cognitive impairment. Multivariate analysis showed that deep cerebral atrophy was independently and significantly associated with cognitive impairment of CSVD (P = 0.024), and hypertension was significantly and independently associated with total MRI burden (P = 0.001).The disease course of arteriolosclerosis CVSD may be related to cognitive function and total MRI burden. Deep cerebral atrophy was an independent risk factor for cognitive dysfunction in arteriolosclerosis CSVD, and hypertension was an independent risk factor for total MRI burden.